Systematic Analysis of Non-coding RNAs Involved in the Angora Rabbit (Oryctolagus cuniculus) Hair Follicle Cycle by RNA Sequencing - Zhao, Bohao; Chen, Yang; Hu, Shuaishuai; Yang, Naisu; Wang, Manman; Liu, Ming; Li, Jiali; Xiao, Yeyi; Wu, Xinsheng (Frontiers in Genetics, 2019)
The hair follicle (HF) cycle is a complicated and dynamic process in mammals, associated with various signaling pathways and gene expression patterns. Non-coding RNAs (ncRNAs) are RNA molecules that are not translated into proteins but are involved in the regulation of various cellular and biological processes. This study explored the relationship between ncRNAs and the HF cycle by developing a synchronization model in Angora rabbits. Transcriptome analysis was performed to investigate ncRNAs and mRNAs associated with the various stages of the HF cycle. 111 long non-coding RNAs (lncRNAs), 247 circular RNAs (circRNAs), 97 microRNAs (miRNAs), and 1168 mRNAs were differentially expressed during the three HF growth stages. Quantitative real-time PCR was used to validate the ncRNA transcriptome analysis results. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses provided information on the possible roles of ncRNAs and mRNAs during the HF cycle. In addition, lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA ceRNA networks were constructed to investigate the underlying relationships between ncRNAs and mRNAs. LNC_002919 and novel_circ_0026326 were found to act as ceRNAs and participated in the regulation of the HF cycle as miR-320-3p sponges. This research comprehensively identified candidate regulatory ncRNAs during the HF cycle by transcriptome analysis, highlighting the possible association between ncRNAs and the regulation of hair growth. This study provides a basis for systematic further research and new insights on the regulation of the HF cycle.